2023
DOI: 10.5114/ceh.2023.128768
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of probiotics in the treatment of minimal hepatic encephalopathy: a systematic review and meta-analysis

Abstract: Aim of the study Patients with minimal hepatic encephalopathy (MHE) have no recognizable clinical symptoms of hepatic encephalopathy (HE), but the mild cognitive and psychomotor deficits have been shown to negatively affect their daily functioning and quality of life. Treatment with probiotics has shown benefit in some clinical trials. This review aimed to systematically analyze the efficacy of probiotics in the treatment of MHE. Material and methods A systematic search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In a recently published phase 2 placebo-controlled, double-blind randomized clinical trial by Bajaj et al [ 30 ], rifamycin SV MMX (RiVM), a nonabsorbable rifampin derivative with colonic action, was effective in reducing ammonia, inflammation, brain oxidative stress, and sarcopenia-related parameters but without significant improvement in cognition. A recent meta-analysis of 9 randomized control trials (RCTs) involving 776 MHE patients by Wibawa et al [ 31 ] indicated that probiotics were more effective in the reversal of MHE and reduced serum ammonia levels in patients with MHE compared to placebo or no treatment, but not more effective than lactulose or l-ornithine-l-arginine (LOLA). Available evidence on the efficacy of probiotic and prebiotic therapy showed mixed results.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…In a recently published phase 2 placebo-controlled, double-blind randomized clinical trial by Bajaj et al [ 30 ], rifamycin SV MMX (RiVM), a nonabsorbable rifampin derivative with colonic action, was effective in reducing ammonia, inflammation, brain oxidative stress, and sarcopenia-related parameters but without significant improvement in cognition. A recent meta-analysis of 9 randomized control trials (RCTs) involving 776 MHE patients by Wibawa et al [ 31 ] indicated that probiotics were more effective in the reversal of MHE and reduced serum ammonia levels in patients with MHE compared to placebo or no treatment, but not more effective than lactulose or l-ornithine-l-arginine (LOLA). Available evidence on the efficacy of probiotic and prebiotic therapy showed mixed results.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…These conflicting results may be partially due to the small size of cohorts or the biased design of individual trials, which could be solved by a meta-analysis. Although there were meta-analyses exploring the effect of probiotics on cirrhosis, most of the studies focused on patients during the progressive period of minimal hepatic encephalopathy (MHE) or HE (18,19). Early detection and timely treatment of cirrhosis are essential to improving the outcomes of cirrhotic patients.…”
Section: Introductionmentioning
confidence: 99%